Li+ Diffusion in Amorphous and Crystalline Al2O3 for Battery Electrode Coatings - Nolan, Adelaide M; Wickramaratne, Darshana; Bernstein, Noam; Mo, Yifei; Johannes, Michelle D (Chemistry of materials, 2021)
Al2O3 is often applied protectively to lithium-ion battery anode and cathode materials to inhibit surface degradation, suppress dendrite formation, and relieve mechanical stresses. Given the very high intrinsic band gap and diffusion barrier of the material, the mechanism that allows Li diffusion through these coatings is not well understood, and widely varying laboratory results indicate that there may be dependencies on morphology and stoichiometry. Using nudged elastic band calculations and ab initio molecular dynamics, we perform a systematic investigation across Al2O3 structures, both crystalline and amorphous, and at various concentrations of Li+ to uncover the optimal parameters for maximally diffusive coatings. We find a correlation between the low proximity of Li+ to Al3+ and the low Li+ migration barrier. Although barriers are the lowest in the highly diffusive one-dimensional channels of crystalline θ-Al2O3, the system is structurally delicate and subject to detrimental distortion as the Li+ content is increased. The α-Al2O3 lattice is, conversely, highly stable against distortion at all Li+ concentrations but disadvantageous for Li+ migration. In amorphous systems, unscreened Li+–Li+ Coulomb repulsion and pre-emptive occupation of “trapping sites” combine to lower the energy barriers as a function of increasing concentration. One of our most important findings is that Al-deficient materials can sharply increase Li+ movement, and we predict that an amorphous material with a combination of high Li+ concentration and Al deficiency would enable highly Li+-conductive protective coatings for electrodes.